Carob (Ceratonia siliqua) leaves: A comprehensive analysis of bioactive profile and health-promoting potential of an untapped resource - Simona Serio; Valentina Santoro; Rita Celano; Donatella Fiore; Maria Chiara Proto; Filomena Corbo; Maria Lisa Clodoveo; Roberta Tardugno; Anna Lisa Piccinelli; Luca Rastrelli (Food Chemistry, 2025)

Biodiversity associated with a coralligenous build-up off Sicily (Ionian Sea) - Gemma Donato; Rossana Sanfilippo; Daniela Basso; Pietro Bazzicalupo; Marco Bertolino; Valentina Alice Bracchi; Mara Cipriani; Francesco D’Alpa; Adriano Guido; Mauro Pietro Negri; Francesco Sciuto; Donatella Serio; et al. (Regional Studies in Marine Science, 2024)

Ecology and Phenology of the Subtidal Brown Alga Sargassum furcatum (Ochrophyta, Fucales), a Likely Non-Indigenous Species from the Mediterranean Sea - Giuliana Marletta; Andrea Lombardo; Donatella Serio (Journal of Marine Science and Engineering, 2024)
This study provides new insights regarding the ecology and phenology of the likely non-indigenous canopy-forming species Sargassum furcatum on the central-eastern coast of Sicily (Italy, Central Mediterranean). This species was described for St. Thomas (Virgin Islands), and it was reported for the first time in the Mediterranean in 1995 in the Chafarinas islands (Spain, western Mediterranean). After the first report, this species was found in 2021 in several sites located along the eastern coast of Sicily (Italy), along the French Mediterranean coastline, in Corsica, and recently also in the Aeolian Islands (Italy). No phenological studies on this species have been ever carried out in the Mediterranean Sea. To conduct this study, a visual census activity was performed in three sites along the Ionian coast of Sicily throughout 2023, during which the length of the main axis of S. furcatum specimens was measured and the frequency of findings of the species during the year was noted. In this study, it was observed that S. furcatum shows a wide adaptability in terms of range of depth, temperature, light exposure, and type of substrate. Since the distribution of this species is mostly centralized in the western Atlantic Ocean, it is likely that S. furcatum entered the Mediterranean through the Gibraltar Strait. Consequently, the entrance of this species in this Basin could be further proof of the ongoing seawater warming and tropicalization of Mediterranean waters. From this point of view, it is important to keep monitoring the dynamics of S. furcatum in the Mediterranean Sea in order to understand its putative impacts on autochthonous communities.

Diversity of Fucales (Ochrophyta, Phaeophyceae) along the Coasts of Lipari and Vulcano (Aeolian Archipelago), Tyrrhenian Sea (Central Mediterranean Sea) - Giuliana Marletta; Andrea Lombardo; Donatella Serio; Silvia Bianchelli (Journal of Marine Science and Engineering, 2023)
This study explored the biodiversity of Fucales along the islands of Lipari and Vulcano, almost ten years after the last studies on the phytobenthos of these islands. To carry out this research, a monitoring activity was conducted through both scuba dives and snorkelling activities. Through this study, a total of 13 species (four belonging to Cystoseira, three to Ericaria, two to Gongolaria, and four to Sargassum) was observed. When comparing the present data with past studies, nine species were previously reported, ten taxa were not found in the present study, and four taxa were reported here for the first time in the Aeolian Archipelago. The alpha (local) diversity was higher in Vulcano than in Lipari. Moreover, the beta (turnover) diversity showed a different assemblage in species grouping between the two islands. Since some of the observed species are currently considered rare or in regression, their finding in the Aeolian Archipelago is of particular interest. Therefore, they should receive special consideration, particularly in light of the possible future establishment of a marine protected area (MPA) in the Aeolian Archipelago.

The Bryozoan Margaretta cereoides as Habitat-Former in the Coralligenous of Marzamemi (SE Sicily, Mediterranean Sea) - Antonietta Rosso; Gemma Donato; Rossana Sanfilippo; Donatella Serio; Francesco Sciuto; Francesco D’Alpa; Valentina Alice Bracchi; Mauro Pietro Negri; Daniela Basso (Journal of Marine Science and Engineering, 2023)
Although several bryozoans are considered habitat-former species, allowing colonisation by epibionts and promoting biodiversity, studies dealt so far with only some, usually constructional, species. In this context, the present study focuses on the epibiosis found on the erect mineralised but flexible species Margaretta cereoides, contributing with some macroalgae to the canopy formation on a coralligenous build-up collected at 36.7 m depth offshore Marzamemi (Ionian Sea, Mediterranean) in the frame of the project CRESCIBLUREEF. Focusing on bryozoans and serpulids we documented high diversity (species richness) on the investigated substrata (M. cereoides, Flabellia petiolata, Peyssonnelia rubra, Osmundaria volubilis and all other fleshy algae including Phyllophora crispa). Diversity, total number of colonies/specimens hosted, and number of colonies/specimens per cm2 are higher on M. cereoides than on algae, possibly in relation with the morphology, robustness and persistence of the surface offered by the bryozoan contrasting with the flexible and ephemeral nature of most algae, often provided with chemical defenses. Bryozoan and even more serpulid epibiont diversity on M. cereoides is also higher than those reported for studied species in the Mediterranean and for Flustra foliacea from North Europe.

Sabellaria alveolata (Annelida, Polychaeta) bioconstructions and associated macroalgal community from Portopalo di Capo Passero (SE Sicily) - ROSSANA SANFILIPPO; DONATELLA SERIO; CLAUDIA DEIAS; ANTONIETTA ROSSO (Mediterranean Marine Science, 2021)
The shallow-water reef building polychaete Sabellaria alveolata is recorded from a new locality in the southeastern corner of Sicily, off Portopalo di Capo Passero. Here, a particular habitat is formed on upper infralittoral rocky bottoms beaten by waves, with S. alveolata developing as veneer-like bioconstructions interspersed/covered with a dense macroalgal community including alien Caulerpa taxa and dominated by Ericaria giacconei. First insights about the development of this particular habitat, as well as observations on possible relationships between Sabellaria and the associated algae, are presented.

Species and habitats of conservation interest in the Ecologically and Biologically Significant Area of the Strait of Sicily: a contribution towards the creation of a Specially Protected Areas of Mediterranean Importance - PIERPAOLO CONSOLI; CHIARA ALTOBELLI; PATRIZIA PERZIA; MARZIA BO; ANTONIETTA ROSSO; GIUSEPPINA ALONGI; DONATELLA SERIO; SIMONEPIETRO CANESE; TERESA ROMEO; FRANCO ANDALORO (Mediterranean Marine Science, 2021)
In 2015, the Strait of Sicily, which includes several banks, was candidate as a future Specially Protected Area of Mediterranean Importance (SPAMI) by the Contracting Parties of the Barcelona Convention. In this context, the present study aims to provide the first biological and ecological characterisation of this poorly known area, focusing on habitats and species of conservation concern. Surveys were carried through a remotely operated vehicle (ROV) and allowed the identification of 19 habitat types, mostly considered of priority interest by the SPA/BD Protocol of the Barcelona Convention. A total of 269 taxa were also identified, mostly Porifera, Cnidaria and Pisces, among which 115 species are of conservation concern according to the International Union for Conservation of Nature (IUCN) Red Lists, the Habitats Directive, the Bern Convention, the SPA/BD Protocol and CITES. ROV surveys allowed some interesting observations on poorly known species and habitats. Results underlined that remarkable discrepancies in species conservation status assessment that exist between the several lists of protected species considered. The IUCN Red Lists, although not legally binding for European States, are the most complete, but, in spite of this, the conservation policies in the EU are largely focused on the Habitats Directive, which is really not exhaustive. An exhaustive and legally binding instrument to protect species of conservation concern at European scale is highly recommended. Acquired results could be useful for the delimitation of a future SPAMI or a network of Marine Protected Areas (including the investigated banks) and the identification of zones within them suitable for different area-based management measures.

Degradation of a photophilic algal community and its associated fauna from eastern Sicily (Mediterranean Sea) - MARCELLO CATRA; GIUSEPPINA ALONGI; RICCARDO LEONARDI; MAURO PIETRO NEGRI; ROSSANA SANFILIPPO; DONATELLA SERIO; ALFIO VIOLA; ANTONIETTA ROSSO (Mediterranean Marine Science, 2019)
The status of the “Biocoenosis of the Infralittoral Algae” of the upper infralittoral zone (at 5 m depth) from two selected stations along the eastern coast of Sicily (Ionian Sea, Mediterranean) was studied with a multiproxy approach involving the study of algae and associated protist and animal organisms, including foraminifers, serpulids, molluscs, bryozoans and ostracods. Scraped samples (40x40 cm) were collected at selected seasons during a 2-year period (2015-2016) in order to identify possible seasonal and spatial differences between the two stations, and to compare present data with historical ones. A community made up of the algae Halopteris scoparia, Padina pavonica, Dictyota dichotoma, Ellisolandia elongata and several other geniculate coralline algae was found in sites historically colonised by a Cystoseira brachycarpa community, which was not found during our study. These algae presently structure the community and provide substratum for several associated epibiotic species. Hierarchical cluster analysis and Non-Metric Multi-Dimensional Scaling Ordination significantly differentiate the communities between the two stations but show no clear seasonal trend. Differences largely relate to changes in the algal vegetation and the impact produced by the regression of structuring species on epibiots (especially serpulids and bryozoans). Comparison with historical algal data from the area indicates the disappearance of Cystoseira brachycarpa, which was present at least until the last ’1990s, and a community degradation with a considerable loss in species richness. This parallels observations in other Mediterranean areas, and could be related to the increase in echinoid population density and their heavy grazing activity.

Marine alien species in Italy: A contribution to the implementation of descriptor D2 of the marine strategy framework directive - GIANNA SERVELLO; FRANCO ANDALORO; ERNESTO AZZURRO; LUCA CASTRIOTA; MARCELLO CATRA; ANTONIA CHIARORE; FABIO CROCETTA; MICHELA D’ALESSANDRO; FRANCESCO DENITTO; CARLO FROGLIA; CINZIA GRAVILI; MARTIN R. LANGER; et al. (Mediterranean Marine Science, 2019)
The re-examination of marine alien species or Non-indigenous species (NIS) reported in Italian Seas by December 2018, is here provided, particularly focusing on establishment success, year of first record, origin, potential invasiveness, and likely pathways. Furthermore, their distribution is assessed according to marine subregions outlined by the European Union (EU) Marine Strategy Framework Directive: Adriatic Sea (ADRIA), Ionian Sea and Central Mediterranean Sea (CMED), and Western Mediterranean Sea (WMED). In Italy, 265 NIS have been detected with the highest number of species being recorded in the CMED (154 species) and the WMED (151 species), followed by the ADRIA (143). Most of these species were recorded in more than one subregion. The NIS that have established stable populations in Italian Seas are 180 (68%), among which 26 have exhibited invasive traits.Among taxa involved, Macrophyta rank first with 65 taxa. Fifty-five of them are established in at least one subregion, mostly in the ADRIA and the CMED. Crustacea rank second with 48 taxa, followed by Polychaeta with 43 taxa, Mollusca with 29 taxa, and Pisces with 28 taxa, which were mainly reported from the CMED. In the period 2012-2017, 44 new alien species were recorded, resulting in approximately one new entry every two months. Approximately half of the NIS (~52%) recorded in Italy have most likely arrived through the transport-stowaway pathway related to shipping traffic (~28% as biofoulers, ~22% in ballast waters, and ~2% as hitchhikers). The second most common pathway is the unaided movement with currents (~19%), followed by the transport-contaminant on farmed shellfishes pathway (~18%). Unaided is the most common pathway for alien Fisshes, especially in CMED. Escapes from confinement account for ~3% and release in nature for ~2% of the NIS. The present NIS distribution hotspots for new introductions were defined on the first recipient area/location in Italy. In ADRIA the hotspot is Venice which accounts for the highest number of alien taxa introduced in Italy, with 50 newly recorded taxa. In the CMED, hotspots of introduction are the Taranto and Catania Gulfs, hosting 21 first records each. The Strait of Sicily represents a crossroad between the alien taxa from the Atlantic Ocean and the Indo-Pacific area. In the WMED, hotspots of bioinvasions include the Gulfs of Naples, Genoa and Livorno.This review can serve as an updated baseline for future coordination and harmonization of monitoring initiatives under international, EU and regional policies, for the compilation of new data from established monitoring programs, and for rapid assessment surveys.

First data on ostracods and foraminifera living in Cystoseira associations in western Ionian Sea - FRANCESCO SCIUTO; ANTONIETTA ROSSO; ROSSANA SANFILIPPO; GIUSEPPINA ALONGI; MARCELLO CATRA; DONATELLA SERIO; SAMEH BEJAOUI; RICCARDO LEONARDI; ALFIO VIOLA (Mediterranean Marine Science, 2018)
For the first time ostracod and foraminifera populations living on infralittoral algae were analysed from three different localities near the Ciclopi Islands Marine Protected Area along the Etnean Ionian coast of Sicily, few km N of the city of Catania. Six series of samples, each of three samples, were collected at 5, 10 and 26 m water depth in sea bottom areas where the Biocoenosis of the Infralittoral Algae is developed. Some samples were collected inside the Ciclopi Islands Marine Protected Area (CIMPA) and some outside it.In all the samples the ostracod association is characteristically constituted by a mixture of true shallow water phytal taxa and and infralittoral sediment-dwelling taxa. The family Xestoleberididae is markedly dominant, mainly in the shallowest samples. Xestoleberis dispar represents more than 60% of all the specimens, followed by X. communis and X. dispar. The families Paradoxostomatidae (with Paradoxostoma rarum, P. simile, P. parallelum, P. intermedium, P. atrum and P. caecum), Hemicytheridae (with Aurila prasina and A. convexa), Bairdidae (with Neonesidea mediterranea, N. corpulenta, and N. Longevaginata) follow. Loxoconchidae (with Loxoconcha rhomboidea), Pontocyprididae (with Pontocypris mediterranea and Pontocypris pirifera) and Cytheruridae (with very few specimens of Semicytherura spp.) are subordinate.Foraminifera are represented almost exclusively by phytal benthic taxa. Between them the the family Miliolidae is markedly prevalent, mostly represented by Quinqueloculina species, followed by the family Rotaliidae with Elphidium crispum, E. depressum, E. aculeatum, and Elphidium spp. Discorbidae, with Rosalina spp.; Cibidididae, largely represented by Cibicides refulgens and C. advenum; Planorbulinidae with Planorbulina mediterranensis, are also present.

The benthic algal flora on rocky substrata of the Tremiti Islands (Adriatic Sea) - Mario Cormaci; Giovanni Furnari; Giuseppina Alongi; Marcello Catra; Donatella Serio (Plant Biosystems, 2000)